ON λ, μ- ZWEIER IDEAL CONVERGENCE IN INTUITIONISTIC FUZZY NORMED SPACE - Khan, Vakeel A; Ahmad, Mobeen (Yugoslav Journal of Operations Research; Vol 30 No 4 (2020), 2020)
In this paper, we study and introduce a new type of convergence, namely (λ, µ)− Zweier convergence and (λ, µ)− Zweier ideal convergence of double sequences x = (xij ) in intuitionistic fuzzy normed space (IFNS), where λ = (λn) and µ = (µm) are two non-decreasing sequences of positive real numbers such that each tending to infinity. Furthermore, we studied (λ, µ)− Zweier Cauchy and (λ, µ)− Zweier ideal Cauchy sequences on the said space and established a relation between them.